2020
DOI: 10.1038/s41598-020-72258-2
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan-like and humic-like fluorophores are extracellular in groundwater: implications as real-time faecal indicators

Abstract: Fluorescent natural organic matter at tryptophan-like (TLF) and humic-like fluorescence (HLF) peaks is associated with the presence and enumeration of faecal indicator bacteria in groundwater. We hypothesise, however, that it is predominantly extracellular material that fluoresces at these wavelengths, not bacterial cells. We quantified total (unfiltered) and extracellular (filtered at < 0.22 µm) TLF and HLF in 140 groundwater sources across a range of urban population densities in Kenya, Malawi, Senegal, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 58 publications
(48 reference statements)
4
11
1
Order By: Relevance
“…In this study, for the microbial community cultures, Peak C was found to be predominantly associated with extracellular material. This is in agreement with the data associated with the bacterial isolates ( Table 3 ) and is also in line with recent environmental observations [ 31 ]. High Peak C intensities are observed within the microbial community culture samples ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, for the microbial community cultures, Peak C was found to be predominantly associated with extracellular material. This is in agreement with the data associated with the bacterial isolates ( Table 3 ) and is also in line with recent environmental observations [ 31 ]. High Peak C intensities are observed within the microbial community culture samples ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 93%
“…As with Peak B, the majority of Peak T fluorescence is observed in the resuspended and lysed cell fractions, indicating the cellular origin of Peak T fluorescence in this laboratory model. This finding challenges recent environmental groundwater research [ 31 ], which concludes that Peak T is predominantly associated with extracellular material [ 8 , 32 , 63 ]. The Peak T data associated with the environmental bacterial isolate monocultures ( Table 3 ) further support this observation.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Protein-like fluorescence (C4, C5) was positively correlated with log-transformed E. coli concentrations in the wet season with highest bacterial loads at high tide (Figure 6). These findings support the notion that tryptophan-like fluorescence intensity may be used as a proxy for degraded water quality determination in wastewater-impacted streams (Baker & Inverarity, 2004;Gu et al, 2020;Mendoza et al, 2020;Sorenson et al, 2020). We found that likely diffuse sources of anthropogenic waste (e.g., septic release, pet waste), indicated by increased bacterial loads, including E. coli, and associated DOM composition, may result in increased microbial utilization of DOM and processing rates in the water column.…”
Section: Urban Sources Of Bioavailable Domsupporting
confidence: 87%